LEGAL PROTECTION FOR HOME WORKERS IN PACKING THE POCI PRODUCTS - Lestari, Siti Duwi; Wardani, Susilo (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
AbstractThe development of the industrialized world and business mechanisms are becoming more efficient, many peoplecan now use labor in a more flexible way toavoid additional costs or fees. This research aims to analyzethe legal relationship between the employer and the homeworker and analyze the legal protection of the fulfillment of the rights of homeworkers in the packing of teabags in the village.legal protection over the fulfillment of the rights of homeworkers in the packing of teapots in Kedawung Village, Tegal Regency.Kedawung Village, Tegal Regency. The method used in this research is juridical and empirical.empirical, Soerjono Soekanto argues that empirical juridical research is a method that connects legal theory with social reality.method that connects legal theory with social reality. This research uses secondary dataThis research used secondary data with data collection method of observation interview. The first research resultshows that the legal relationship that occurs between employers and home workers is based on an ordinary civil agreement.homeworkers is based on ordinary civil agreements and is not an employment relationship as in Law No. 13/2003.homeworkers are workers in a company who carry out production activities outside the company's premises.workers in a company who carry out production activities outside the company environment at home or at the location of an association.outside the company's premises at home or at the location of a community gathering with a putting out system.where they work on some of the stages of production outside the Company and areare paid based on the unit wage produced and do not receive other rights as formal workers.as formal workers. The second shows that even though home-based workerswork part of the production stages of the company, but do not getm Translated with DeepL.com (free version)